Experimental Investigation of Interaction Effects in Foam-Filled Thin-Walled Aluminum Tubes - Güden, Mustafa; Toksoy, Ahmet Kaan; Güden, Mustafa; Kavi, Halit; Kavi, Halit (Springer Verlag, 2006)
The interaction coefficients of polystyrene foam filling of thin-walled aluminum cylindrical tubes were investigated experimentally through compression testing of partially foam-filled tubes with and without adhesive. The experimental load-displacement curves and observation of the crushed sections of filled tubes have shown that partial foam filling reduced the fold length and hence increased the average crushing loads of tubes, proving the interaction effect between tube wall and filler. The interaction coefficients for the partial foam filling were further calculated to be in the level and/or higher than that of the foam plateau load of transverse direction.
Keywords: Aluminum tubes; Foamed materials; Compression